COST-VOLUME-PROFIT CALCULATION ANALYSIS AS A PROFIT PLANNING APPROACH IN “MARKISA MANIS MAMPANG” MICRO BUSINESS DEPOK CITY, WEST JAVA PROVINCE - Dyah Mieta Setyawati; Susanti Usman; Feny Fidyah (SEAN Institute, 2023)
Analysis of the calculation of Cost-Volume-Profit (CVP) aims to identify problems related to sales at the business planning stage using the Contribution Margin, Break-Even Point (BEP), Margin of Safety (MOS), Degree of Operating Leverage (DOL) and planning approaches. profits targeted by business actors. The research method used is a quantitative descriptive method. The data used is primary data in the form of business reports